2013
DOI: 10.1152/ajpheart.00543.2012
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 15 impairs aortic contractile and relaxing function through altered caveolar signaling of the endothelium

Abstract: Mazagova M, Buikema H, Landheer SW, Vavrinec P, van Buiten A, Henning RH, Deelman LE. Growth differentiation factor 15 impairs aortic contractile and relaxing function through altered caveolar signaling of the endothelium. Am J Physiol Heart Circ Physiol 304: H709 -H718, 2013. First published December 21, 2012 doi:10.1152/ajpheart.00543.2012.-Growth differentiation factor 15 (GDF15) is an independent predictor of cardiovascular disease, and increased GDF15 levels have been associated with endothelial dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…4 By comparing endothelial function in wild type and GDF-15 knocked out mice GDF-15 was recently demonstrated to directly modulate the endothelial-dependent NO synthase pathway in the aortas of mice. 31 Our observations are also in agreement with other lines of evidence suggesting a significant role of GDF-15 in vascular brain injury. For instance, higher GDF-15 levels have previously been reported to be strongly related to worse functional status in the acute phase of ischemic stroke in humans.…”
Section: Discussionsupporting
confidence: 92%
“…4 By comparing endothelial function in wild type and GDF-15 knocked out mice GDF-15 was recently demonstrated to directly modulate the endothelial-dependent NO synthase pathway in the aortas of mice. 31 Our observations are also in agreement with other lines of evidence suggesting a significant role of GDF-15 in vascular brain injury. For instance, higher GDF-15 levels have previously been reported to be strongly related to worse functional status in the acute phase of ischemic stroke in humans.…”
Section: Discussionsupporting
confidence: 92%
“…GDF-15 has been introduced as a biomarker for cardiovascular events and ­cardiovascular risk stratification [42-44] and several vascular diseases including STEMI [42], coronary artery disease [43, 45], stroke [46] as well as renal and cardiac damage in general [47-49]. In addition to its value as a surrogate parameter, an active role in atherosclerosis and other vascular pathologies has been suggested [50, 51]. Whether the lowered GDF-15 production in cells incubated with HRO serum is causally involved in vascular calcification is speculative, as its role in cardiovascular disease is still unclear and not sufficiently examined.…”
Section: Discussionmentioning
confidence: 99%
“…118 Increased adhesion molecule expression, reduced anticoagulant properties, and imbalanced production of vasodilating and vasoconstriction substances all lead to endothelial dysfunction. 119 There are sufficient indications that GDF15 causes endothelial dysfunction by impairing vascular contraction and relaxation, which consequently could have a large impact on the function of the heart, by inducing not only large artery disease but also microvascular disease, which is associated with a deteriorating cardiac function. 120 Mechanistically, Mazagova et al 119 showed that the vascular contractility in response to vasoconstrictor agents was repressed under presence of GDF15, suggesting that GDF15 affects the NO system in endothelial cells.…”
Section: Effect Of Growth Differentiation Factor 15 On Endothelial Cellsmentioning
confidence: 99%